Anaesthetic management of postural orthostatic tachycardia syndrome presenting during pregnancy. (August 2019) - Harding, F.; Hyndman, N.; Burns, R.
Highlights: Postural orthostatic tachycardia syndrome (POTS) First case report of POTS developing during pregnancy. Post-viral POTS with associated 2:1 heart block. Severe haemodynamic instability due to POTS in pregnancy.